Comparison of radiofrequency ablation and surgery for thyroid papillary microcarcinoma: efficacy, safety and life quality - Kong, Xiaoyan; Wang, Liangchen; Sun, Yuchen; Zhu, Di; Yang, Caizhe (Frontiers in Endocrinology, 2024)
Objective: To compare the efficacy, safety and patients' quality of life of radiofrequency ablation (RFA) and surgery in the treatment of papillary thyroid microcarcinoma (PTMC). Methods: MEDLINE, EMBASE, Cochrane, CNKI and other databases were searched for studies on radiofrequency ablation versus traditional surgery for PTMC up to October 2022. RevMan5.4 software was used for Meta-analysis.Results: 10 articles were selected from 392 articles, including 873 cases of radiofrequency ablation and 781 cases of open surgery. After meta-analysis, the incidence of postoperative complications in the radiofrequency ablation group was lower than that in the surgery group, and the difference was statistically significant [OR=0.24, 95%CI (0.14,0.41), P＜0.001 ]. There were no significant differences in lymph node metastasis rate, local recurrence rate, and new tumor rate between the two groups [ OR=1.6, 95%CI (0.21，12.41)， P＞0.05; OR=0.85， 95%CI (0.05, 13.8)， P ＞ 0.05; OR=0.12 ， 95%CI (0.01 ， 0.98) ， P ＞ 0.05]. The treatment time and hospital stay in the radiofrequency ablation group were shorter than those in the open surgery group [MD=-49.99，95%CI (-62.02，-37.97)，P＜0.001；MD=-5.21， 95%CI(-7.19,-3.23),P<0.001], and the cost was significantly lower than that of the traditional surgery group [SMD=-14.97，95%CI (-19.14，-10.81)，P＜0.001]. The quality of life of patients in the radiofrequency ablation group was higher than that in the surgery group [MD=-1.61，95%CI (-2.06，-1.17)，P＜0.001]. Conclusions: Compared with traditional open surgery, radiofrequency ablation for papillary thyroid microcarcinoma has the advantages of less trauma, fewer complications, faster recovery and higher quality of life. The indications need to be strictly controlled in the treatment.